Women’s Leadership in the Light of Islamic Law: Normative and Contextual Perspectives - Muhammadong Muhammadong; Khaerunnisa Khaerunnisa; Farhah Utami; Sitti Muthmainnah; Dalilul Falihin (Matan : Journal of Islam and Muslim Society, 2026)
This study discusses women’s leadership from the perspective of Islamic law through normative and contextual analysis. The background of this research is based on continuing differences of opinion regarding the permissibility of women occupying leadership positions, whether in domestic, social, political, or governmental spheres. Some perspectives understand women’s leadership textually as something limited, while others emphasize the values of justice, public benefit, and competence as the main foundations of leadership. The methodology used is normative legal research with conceptual, historical, and contextual approaches. Data were obtained through literature study of the Qur’an, hadith, scholarly opinions, and contemporary Islamic legal literature. The findings show that Islamic law does not absolutely prohibit women from becoming leaders, as long as such leadership is carried out based on the principles of trustworthiness, justice, consultation, capability, and public welfare. Differences among scholars are largely influenced by the social, cultural, and political contexts of particular periods. The study concludes that women’s leadership can be accepted within the perspective of Islamic law if it fulfills moral, intellectual, and professional requirements. Therefore, the assessment of women’s leadership should be carried out proportionally, not merely based on gender, but on capacity and public benefit.